Vitexin induces apoptosis through mitochondrial pathway and PI3K/Akt/mTOR signaling in human non-small cell lung cancer A549 cells - Liu, Xiaoli; Jiang, Qingfeng; Liu, Huaimin; Luo, Suxia (Biological research, 2019)
Currently, the prognosis of patients with non-small cell lung cancer (NSCLC) remains dismal; hence, it is critical to identify effective anti-NSCLC agents with limited side effects. This study aimed to evaluate the therapeutic potential of flavonoid compound vitexin in human NSCLC cells and the underlying mechanisms. The experimental results indicated that vitexin reduced the viability of A549 cells in a dose-dependent manner with nearly no toxicity against normal human bronchial epithelial 16HBE cells. Vitexin also dose-dependently increased A549 cell apoptosis, accompanied by the decreased Bcl-2/Bax ratio and the increased expression of cleaved caspase-3. Moreover, the in vivo anticancer activity of vitexin was further determined in nude mice bearing A549 cells. In addition, vitexin induced the release of cytochrome c from the mitochondria to the cytosol and the loss of mitochondrial membrane potential. Vitexin also significantly reduced the levels of p-PI3K, p-Akt and p-mTOR, and the pro-apoptotic effect of vitexin on A549 cells was partly blocked by SC79, an Akt activator. Accordingly, we believed that vitexin could be used as a potential therapeutic agent for the treatment of NSCLC in the future.